The moderator role of decision-making styles on relationship between personality and drug dependence vulnerability - Rahmanian, Mahdieh; Hasani, Jafar; Zamani, Maryam; Niaei, Amir Maziar (Researcher Bulletin of Medical Sciences, 2019)
Background: According to recent researches, decision-making style and personality traits play an important role in the drug dependence vulnerability. The aim of current research was to investigate the moderator role of decision-making styles on relationship between personality and drug dependence vulnerability. Materials and Methods: Two hundred and twenty students of Tehran Payame Noor University were selected randomly and completed NEO big five personality scale, general decision-making style questionnaire and risk of addiction questionnaire. The data were analyzed using hierarchical regression analysis. Results: The results of present study indicated that only neuroticism is able to predict risk of addiction. In addition, intuitive, dependent, spontaneous and avoidant decision-making style moderated the relationship between neuroticism and drug dependence vulnerability. Conclusions: The results showed that by changing the decision-making style, it is possible to prevent substance dependence disorders in vulnerable populations.